The Cipher of Nature in Kant’s Third Critique: How to Represent Natural Beauty as Meaningful? - Godess-Riccitelli, Moran (Con-Textos Kantianos. International Journal of Philosophy, 2020)
What is it that we encountered with in our aesthetic experience of natural beauty? Does nature “figuratively speaks to us in its beautiful forms”,2 to use Kant’s phrasing in the third Critique, or is it merely our way of interpreting nature whether this be its purpose or not? Kant does not answer these questions directly. Rather, he leaves the ambiguity around them by his repeated use of terminology of ciphers when it comes to our aesthetic experience in nature. This paper examines Kant’s terminology of ciphers in the Critique of Judgment and demonstrate through it the intimate link aesthetic experience in natural beauty has with human morality. A link whose culmination point is embodied in the representation of beauty as a symbol of morality.
Keywords: Aesthetic experience; Aesthetic judgment; Critique of Judgment; Figurative language; Morality; Natural beauty